Morfem Bahasa Melayu Riau Dialek Siak di Desa Rempak Kecamatan Sabak Auh Kabupaten Siak Provinsi Riau - Nazira, Mira (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2018)
This study of “Morpheme Malay Riau Dialect Of Siak In The Village OfUnisow Subdistrict Sabak Auh Siak, Riau Province”. The problem in this research is how the morphemes are bound, which are in malay Riau Province? This study iams to collect, analyze, deserige and concluede morpheme bound contained in the Malay Riau dialect of Siak in the Village Of Unison Subdistrict Sabak Auh Siak Regency Of Riau Province. The main data souvees in dualitative research is the speech of informans who originated from the Malay Riau Dialect Of Siak In The Village Of Unision Subdististrict Sabak Auh Siak Regency Of Riau Province. The data obtained in this study is a morpheme gound to that contained in the utterance that is pronounced by the informant. The method that I use in the implementation of this research method descriptive. Data collection techniques this research uses observasion techniques, interviews, recordings, listen and record. From the results obtained it can be concluded that the morpheme malay Riau dialect of Siak in the village of unison Subdistrict Sabak Auh Siak regency of Riau Province consists of (1) Prefix (prefix), hit, search, split, divide, paint, crusty, hanging, gilard, forgetful, destroyer, for, will, (2) Infiks (insert), bars, cruising (3) suffixes (ending), love, reconcile, food, (4) confix (prefix and suffix), cleverness, planning, coming.